1997
DOI: 10.1097/00007890-199712270-00015
|View full text |Cite
|
Sign up to set email alerts
|

Posttransplant Diastolic Hypertension

Abstract: These data support the hypothesis that posttransplant diastolic hypertension is a result of TGF-beta-induced, endothelin-mediated arteriolar vasoconstriction and subsequent activation of the renin-angiotensin pathway. These effects are independent of immune-mediated graft injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

1999
1999
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…The authors did not speculate on the mechanism of the tacrolimus overdose‐related myocardial ischemia. Tacrolimus increases endothelin release from vascular endothelium (8, 9). Endothelin causes arterial vasoconstriction (12).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors did not speculate on the mechanism of the tacrolimus overdose‐related myocardial ischemia. Tacrolimus increases endothelin release from vascular endothelium (8, 9). Endothelin causes arterial vasoconstriction (12).…”
Section: Discussionmentioning
confidence: 99%
“…However, one case report described myocardial ischemia following tacrolimus overdose in a bone marrow transplant recipient (7). Tacrolimus increases endothelin, a potent vasoconstrictor, release from the vascular endothelium (8, 9). These findings suggest that tacrolimus may cause hypertension, nephrotoxicity, and possibly myocardial ischemia through its potential vasoconstrictive activity.…”
mentioning
confidence: 99%
“…[3][4][5][6][7] Posttransplantation diastolic hypertension has been attributed to TGF-␤ induction and resulting endothelinmediated renal arteriolar vasospasm and reninangiotensin pathway activation. 79 By reducing renal hypertension and systemic vasoconstriction, calcineurin-inhibitor-sparing regimens may be expected to decrease these risks as well as to improve long-term graft survival.…”
Section: Theoretical Benefitsmentioning
confidence: 99%
“…CsA is known to cause numerous unwanted side effects. It has been shown that CsA increases Ang II receptors independently from CaN inhibition, which causes vasoconstriction and systemic hypertension and can promote CH [ 35 , 45 47 ]. This may be due to CsA alleviating the cardioprotective action of CnA β .…”
Section: Discussionmentioning
confidence: 99%